1987
DOI: 10.1177/014107688708000906
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year follow up of Patients Treated with Inpatient Psychotherapy at the Cassel Hospital for Nervous Diseases

Abstract: Twenty-eight patients who were admitted consecutively to a single-adult unit of the Cassel Hospital in 1977/8 were followed up 5 years after discharge. Those who were found to have improved at the end of treatment remained well 5 years later. These could be distinguished by their combination of neurotic psychopathology, considerable depression, superior intelligence, and lack of a chronic outpatient history. Patients who had improved 5 years after discharge did not show these characteristics, but had all spent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…An earlier retrospective study carried out at the Cassel Hospital in the 1980s found that ‘neurotic’ individuals had better outcomes than more disturbed patients who suffered from ‘borderline’ disorders [26]. It is possible that changes in the inpatient therapeutic program did not keep pace with change in hospital clientele, which shifted from a mainly chronically neurotic group of mild to moderate severity to a borderline group of greater severity of presentation.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier retrospective study carried out at the Cassel Hospital in the 1980s found that ‘neurotic’ individuals had better outcomes than more disturbed patients who suffered from ‘borderline’ disorders [26]. It is possible that changes in the inpatient therapeutic program did not keep pace with change in hospital clientele, which shifted from a mainly chronically neurotic group of mild to moderate severity to a borderline group of greater severity of presentation.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few studies on the outcome of treatment of patients with a chronic personality disorder which include either a full economic evaluation or an assessment of degree of health service utilization as one of the main variables. In a retrospective study Rosser et al (1987) showed that the net gain for the whole sample under study (28 patients) was approximately £700,000 for patients who satisfactorily completed treatment at the Cassel Hospital. Stevenson & Meares (1992) reported that the amount of prescribed and unprescribed drugs used, the number of medical visits and hospital admissions, the length spent as an inpatient and the amount of time away from work, significantly decreased after one year twice weekly individual psychoanalytic psychotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The 15 families who either left treatment or were discharged from hospital in the first eight weeks of admission cannot be considered as engaging in the treatment offered on the unit. Denford et al (1983) classified six of the 28 patients in their study of in-patient psychotherapy at the Cassel Hospital as drop-outs from treatment, and a further eight as treatment failures at the time of discharge, On follow-up five years later by Rosser et al (1987) six patients (two drop out, four failure on discharge) were considered to be`late successes'. There were no`late failures' identified.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of neurotic psychopathology, superior intelligence, considerable depression, and minimal previous out-patient treatment were identified as predictors of favourable outcome. Rosser et al (1987) followed these same patients up five years later and found that patients who had improved had the capacity to form close and helpful relationships, they were less dependent on the Health Service, and their economic productivity was enhanced.…”
Section: Introductionmentioning
confidence: 99%